2023
DOI: 10.1126/scitranslmed.adg1656
|View full text |Cite
|
Sign up to set email alerts
|

Gut-licensed β7 + CD4 + T cells contribute to progressive retinal ganglion cell damage in glaucoma

Chong He,
Wenbo Xiu,
Qinyuan Chen
et al.

Abstract: Glaucoma is the leading cause of irreversible blindness. Currently, most therapeutic strategies aim to reduce elevated intraocular pressure (EIOP), but this does not always halt disease progression. Evidence suggests a role for T cells in glaucoma pathogenesis, but the underlying mechanisms remain largely unknown. Here, we found that the percentage of circulating CD4 + T cells expressing a gut-homing integrin β7 was increased in patients with glaucoma and was associated with disease sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous reports implicate a T-cell response in glaucoma pathogenesis ( 20 , 44 , 45 ). Hence, we aimed to determine whether the pan T-cell marker CD3 could be detected in the retinae of the experimental groups via immunohistology.…”
Section: Resultsmentioning
confidence: 91%
“…Previous reports implicate a T-cell response in glaucoma pathogenesis ( 20 , 44 , 45 ). Hence, we aimed to determine whether the pan T-cell marker CD3 could be detected in the retinae of the experimental groups via immunohistology.…”
Section: Resultsmentioning
confidence: 91%
“…While the innate immune system has long been linked to glaucoma through glial cells and oxidative stress, the findings support the role of the adaptive immune system [ 64 ]. Studies have shown that CD4+ T cells can facilitate RGC death [ 65 ], and an imbalance in Treg cells/T17 cells has been observed in experimental autoimmune optic neuritis, a condition sharing similarities with glaucoma [ 66 ]. Studies indicate a correlation between immune potency and resistance to RGC death, suggesting immune dysfunction as a potential condition for glaucoma development [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 Another study demonstrated the significant role of gut-homing β7 + CD4 + T cells in retinal ganglion cell damage in glaucoma in both human and mouse models. 13 14 This finding highlights the complex interplay of the gut-retina axis in the pathophysiology of glaucoma. While emerging evidence from some observational studies suggests an association between GM dysregulation and glaucoma, whether there is a causal relationship between GM composition and glaucoma risk remains to be established.…”
Section: Introductionmentioning
confidence: 86%